Evaluating the effect of Balanced Scorecard model (BSC) on performance of Health, Safety and Environment Management System (HSE-MS): (A Case Study) - mahnaz azimi; shahram vosoughi; mohammadreza miri lavasani (Salāmat-i kār-i Īrān, 2017)
Background and aims: However, both the implementation and establishment of the Health, safety and Environment (HSE) management system is successful, but there is no guarantee on the quality of its performance. Therefore, a comprehensive performance evaluation system is essential for monitoring, evaluating and continuous improvement of these systems. If this evaluations are based on companychr('39')s strategic planning, they are on the right path. The aim of this study was to evaluate the impact of the implementation of the Balanced Scorecard (BSC) on improvement of HSE management system in one of a big production companies in our country.